Recent Development in Pulmonary Valve Replacement after Tetralogy of Fallot Repair: The Emergence of Hybrid Approaches - Suleiman, Tariq; Kavinsky, Clifford J.; Skerritt, Clare; Kenny, Damien; Ilbawi, Michael N.; Caputo, Massimo (Frontiers in Surgery, 2015)
In the current era approximately 90% of infants born with tetralogy of Fallot (ToF) are expected to live beyond 40 years of age making it the fastest growing population amongst patients with congenital heart disease. One of the most common late consequences after repair of ToF, is pulmonary valve regurgitation (PVR). Significant PVR results in progressive dilatation and dysfunction of the right ventricle, decrease in exercise tolerance, arrhythmias, heart failure, and increased risk of sudden death. The conventional approach of dealing with this problem is to perform pulmonary valve replacement using cardiopulmonary bypass (CPB) and cardioplegic arrest. However, this approach is associated not only with long operative times but also side effects related to the use of CPB. Development of percutaneous approaches to valve disease is one of the most exciting areas of research and clinical innovation in cardiovascular research. The main development has been that of transcatheter pulmonary valve replacement for the rehabilitation of conduits between the right ventricle and pulmonary artery in patients after surgery for ToF. However, with the percutaneous technique, a limited size of prosthesis can be inserted. Moreover, the technique does not offer the opportunity of treating additional defects that are frequently associated with severe PR, such as pulmonary artery dilatation, and it cannot be used in the significantly dilated native right ventricular outlet tract (RVOT). The advent of the hybrid surgical options for treating cardiac disease has integrated the techniques of interventional cardiology with the techniques of cardiac surgery to provide a form of therapy that combines the respective strengths of both fields. In this review, we present and compare recent advances in procedures to replace the pulmonary valve in patients with ToF presenting with severe PVR and dilated RVOT.